DESIGN AND IMPLEMENTATION OF A WEATHER MONITORING SYSTEM FOR AN INTERNET OF THINGS (IOT)-BASED AGRICULTURAL CALENDAR SYSTEM - Nurindra, Fitra
To build predictions for an agricultural calendar, a system that can accurately acquire weather data from a farming area is needed. Additionally, the system must be able to transfer data to and from the cloud. It should also anticipate usage in remote farming areas where electricity from the national grid (PLN) might not be available. Thus, the system needs to use a power supply from renewable energy sources, specifically solar energy. This paper explains the design and implementation of a weather monitoring system for an IoT-based agricultural calendar system. The designed system consists of sensor nodes that can measure weather parameters in a farming area such as air temperature, air pressure, air humidity, soil moisture, sunlight intensity, wind direction, wind speed, and rainfall. This weather data will then be sent to the cloud by a gateway periodically every 30 minutes to be further processed into weather predictions in the agricultural calendar system. The gateway designed for this system uses a ESP-NOW protocol to communicate with the irrigation system and a 4G network to communicate with the cloud server. Additionally, the gateway has local storage to save weather data that fails to be sent to the cloud due to an internet connection outage. The system uses two power sources: power from the PLN and solar energy, ensuring the system can function even when PLN electricity is down. In the design and implementation, the weather monitoring system can already perform its main functions, which are measuring weather parameters in the farming area and transferring data to the cloud periodically. Furthermore, the accuracy level of the weather data measured by this system meets the specified criteria, with air temperature accuracy (±0.2°C), air humidity (±1% RH), sunlight intensity (±2% lux), and wind speed (±0.1 m/s). However, this system still requires further development and testing to improve the accuracy of other weather data and to develop an enclosure that ensures the weather monitoring system meets the IP65 specification for optimal outdoor use.